Imaging of bone using infrared radiation - Swetha Arulmozhi, R; Vaidya, Mahima; Sahana, S; Srinithi, S; Rajalakshmi, T (International Journal of Engineering and Technology, 2018)
Imaging of bone helps to identify cortical abnormalities and associated deformities. This paper aims at providing a simple device that uses non ionizing radiations from a near infrared source which can detect changes in bone shape or any related fractures. The circuit is very simple and of relatively low cost. As per the data health in India, it is seen that 30% of the total population is prone to low bone density. This is an alarming situation that led to design of this paper. The device comprises of 17 NIR LED (850 nm) and c170 Logitech 5MP web camera, with its IR filter removed. The LED array is used as the source and the camera as the detector. The light beam from the source is focused on the desired region of the skin. The source and the camera are positioned mutually perpendicular to the region of the skin to be imaged for acquisition of a perfect image of bone. The image obtained is further processed by contrast enhancement and adaptive histogram equalization. The enhanced image is studied further for bone fractures, abnormalities, etc. An attempt is also made to focus on extending this technique as a screening tool for persons affected with Fibromyalgia.